Early increase of cerebrospinal fluid 14-3-3ζ protein in the alzheimer's disease continuum - Lu, Yuanyuan (Frontiers in Aging Neuroscience, 2022)
Background The earlier research has shown that the 14-3-3ζ is increased in neurofibrillary tangles (NFTs) of human Alzheimer's disease (AD) brains and stimulates the tau phosphorylation. Cerebrospinal fluid (CSF) 14-3-3ζ along the AD continuum remains to be explored. Methods We analyzed 113 cognitive normal (CN) controls, 372 patients with mild cognitive impairment (MCI), and 225 patients with AD dementia from the Alzheimer's Disease Neuroimaging Initiative database. CSF 14-3-3ζ protein was measured by Mass Spectrometry. Results We observed higher CSF 14-3-3ζ in the MCI group vs. the CN group and in the AD group vs. the MCI or CN group. The 14-3-3ζ was able to distinguish AD from CN and MCI. High 14-3-3ζ predicted conversion from MCI to AD. In CSF, phosphorylated tau at threonine 181 and total-tau were associated with 14-3-3ζ in MCI and AD groups, and beta-amyloid (Aβ) 42 correlated with 14-3-3ζ in the MCI group. Baseline high 14-3-3ζ was associated with cognitive decline, brain atrophy, glucose hypometabolism, and Aβ deposition in MCI and AD at baseline and follow-up. Conclusion Our findings revealed the potential diagnostic and prognostic utility of CSF 14-3-3ζ in the AD continuum. The 14-3-3ζ could be a promising therapeutic target for the intervention of AD.